Старик Хоттабыч - Лагин Лазарь Иосифович (Школьная библиотека, 2015)
Экземпляры: ДБ (20170410) / Инвентарный номер: 53841 / Цена: 120.00 / Сис.шифр: Р2ср / Авт.знак: Л 14 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6